CERITA RAKYAT “DEWI RENGGANIS”: KAJIAN FEMINIS - Musyarrof, Ahmad; Fitriani, Intan; Fauziyah, Syifa (ppjbsip, 2023)
Abstract: This research aims to understand the role and status of Dewi Rengganis in society, as well as describe the community's perspective in folk stories involving this female character. The research utilizes a qualitative descriptive text analysis method with a postmodern feminist approach. The objective of this approach is to interpret the position and role of women in society. The results of the study indicate that in the legend of Dewi Rengganis, the role and position of women can be confirmed by reintroducing female characters who exist as subjects, have autonomy, and possess the ability to exercise their power. Through this interpretation, the folk tale of Dewi Rengganis serves as a tool to elevate the status and role of women in society. The implications of this research are that Indonesian folklore and folk literature have great potential in promoting gender equality and dismantling demeaning stereotypes against women. By introducing strong and influential female characters like Dewi Rengganis, society can see that women have equal potential to achieve success and play significant roles in society. This research provides new insights into the role of women in Indonesian folklore and encourages the development of inclusive narratives that depict gender diversity. Further implications may include changes in societal attitudes towards women, empowerment of women in various fields, and strengthening awareness of the importance of gender equality in society.